Phenotypic and genotypic comparison of ESBL production by Vaginal Escherichia coli isolates from pregnant and non-pregnant women - Al-Mayahie, Sareaa MG (BioMed Central, 2013)
BACKGROUND: Vaginal Escherichia coli is a reservoir along the fecal-vaginal-urinary/neonatal course of transmission in extraintestinal E. coli infections. They also causes genital tract infections especially vaginitis, so that detection of their antibiotic resistance is an important approach to control these infections. One important mechanism of resistance is ESBL production by Enterobacteriaceae especially Klebsiella spp. and Escherichia coli, which is now a worldwide problem that limits therapeutic options. METHODS: Sixty one vaginal E. coli isolates from pregnant and non-pregnant women, were detected phenotypically and genotypically for ESBL production. RESULTS: Most of pregnant and non-pregnant women's isolates, were resistant to cefotaxime (100% vs. 81.5%, respectively) and more than half of them to ceftazidime (56.5% vs. 71.0%, respectively). One hundred percent each, 52.1% vs. 68.4%, and 73.9% vs. 60.5%%, were ESBL producers by screening, confirmatory, and PCR tests, respectively. Pregnant women's isolates had: CTX-M- (69.5%), SHV- and OXA-type (each 4.3%) ESBLs. Only one isolate (4.3%) had two types of ESBLs. All 16 CTX-M-positive (100%) isolates had CTX-M-1. Non-pregnant women's isolates were predominated by SHV and CTX-M -type (44.7% vs. 39.4%, respectively), followed by OXA- (15.7%), and TEM-type (2.6%). Of these isolates, 42.1% had two types of ESBL genes. All 15 CTX-M-positive (100%) isolates had CTX-M-1. Pregnant and non-pregnant women's isolates differed significantly (P≤ 0.05) regarding the expression of SHV- (4.3% vs. 44.7%, respectively) and CTX-M-type (69.5% vs. 39.4%, respectively) ESBLs. In both, CTX-M-1 was the predominant CTX-M group (each 100%). All of the isolates were susceptible to imipenem and meropenem, while the highest rate of resistance was against β-lactams. Multidrug resistance was noted in 56.2% of ESBL-producing isolates. CONCLUSIONS: Ggenital tracts of pregnant and non-pregnant women represent different environments for propagation of ESBL-producing E. coli. In Iraq, nationwide study is required to make a precise estimation of this widespread of ESBL-producing bacteria.